Performance and Heavy Metal Leaching Behavior of Bituminous Fly Ash-Based Geopolymer in Aggressive Environments - Parichat Muensita; Suwimol Asavapisit; Rungroj Piyaphanuwat (Environment and Natural Resources Journal)
This article investigates the performance of a geopolymer synthesized from bituminous fly ash (BFA) activated with sodium hydroxide. The BFA-based geopolymer (BFAG) exhibited high mechanical strength and a densified microstructure. The optimal SiO2/Al2O3 and Na2O/SiO2 molar ratios were found to be 3:1 and 0.2, respectively, yielding a 28-day compressive strength of 9.65 MPa. The inclusion of 30wt.% of a PS material containing heavy metals led to a substantial reduction in strength by 56% and 73% compared to samples with the SiO2/Al2O3 molar ratio of 2:1 and 3:1, respectively, at 28 days. The ability of the BFAG matrix to contain 30wt.% PS was evaluated using a waste extraction test (WET). The leaching behavior of heavy metals from the BFAG matrix was assessed with three aggressive leachants: sodium citrate, sodium acetate, and synthetic acid rain. Results showed that, under exposure to these leachants, the leached concentrations of Cr, Fe, and Zn from samples with the SiO2/Al2O3 ratio of 3:1 were lower than those from samples with the 2:1 ratio, with concentrations ranging from 0.32-1.73, 3.07-6.67, and 152-284 mg/L, respectively. Despite exposure to harsh conditions, the BFAG matrix effectively immobilized over 99% for Cr and Fe and Zn, except when exposed to sodium citrate which only retained 98.5% of Zn. BFAG can be used to treat heavy metal and heavy metal-contaminated sludge. This matrix reduces environmental exposure, thereby decreasing heavy metal leaching into the environment before safe disposal in landfills. BFAG can also be used as a cement substitute in the solidified process, which lowers treatment costs and reduces cement consumption. It can decrease carbon dioxide emissions from cement production.